Analisis Conjoint Preferensi Konsumen terhadap Kombinasi Fitur Produk Motor Bekas Berdasarkan Segmen Gender di Jambi - Apriyanti, Apriyanti (Bina Nusantara University, 2013)
The purpose of this study is to determine consumer preferences for product attributes of used motorcycles. It is because motorcycles have so many variants that make consumers confused in choosing the products. Therefore, company should know what is required by the consumer to distinguish between men and women. This study used Cochrant Q Test and Conjoint Analysis aiming to evaluate the characteristics of the motorcycle product attributes considered by consumers when buying a used motorcycle. The results of this study indicate, from 13 attributes considered by consumers to buy a used motorcycle, 6 considered the most important attribute is price, design, color, safety, fuel efficiency, and durability of the motorcycle. Men desired a combination of motorcycle price 5-7 million, classical design, having security alarm, dominant color, economic fuel, and durability of the body. As for women is a combination of motorcycle price <5 million, classical design, having security alarm, dominant color, economic fuel, and durability of the body.